Pengaruh Orientasi Pasar dan Inovasi Produk terhadap Kinerja Pemasaran UMKM Makanan Ringan di Kecamatan Caringin, Kabupaten Bogor - Ahmad Roihan Allutfi; Yulianingsih Yulianingsih; Palahudin Palahudin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of market orientation and product innovation on the marketing performance of Micro, Small, and Medium Enterprises (MSMEs) in the snack food sector located in Caringin District, Bogor Regency. The background of this research is the increasing competition in the snack food industry, which requires MSMEs to adapt to market demands and continuously develop innovative products to sustain their competitiveness. The research employed a quantitative approach with descriptive and verification methods to provide a comprehensive understanding of the relationship between the studied variables. A total of 81 MSME actors were selected as respondents using a proportional stratified random sampling technique to ensure fair representation of the population. Data collection was carried out through structured questionnaires and documentation to capture both subjective perceptions and objective evidence. The data were then analyzed using multiple linear regression analysis to test the proposed hypotheses. The findings reveal that market orientation and product innovation have significant effects, both partially and simultaneously, on the marketing performance of MSMEs in the snack food sector. Specifically, market orientation enhances the ability of MSMEs to understand customer needs, competitor strategies, and market dynamics, while product innovation contributes to offering unique, varied, and competitive products that meet consumer expectations. The study concludes that strengthening market orientation and encouraging continuous product innovation should be considered as strategic priorities for MSMEs to achieve superior marketing performance. These results provide practical implications for MSME owners and policymakers to design programs and interventions that foster competitiveness and long-term business sustainability.